2018
DOI: 10.1162/jocn_a_01277
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Encoding of Effort and Reward throughout the Execution of Action by External Globus Pallidus Neurons in Monkeys

Abstract: Humans and animals must evaluate the costs and expected benefits of their actions to make adaptive choices. Prior studies have demonstrated the involvement of the basal ganglia in this evaluation. However, little is known about the role of the external part of the globus pallidus (GPe), which is well positioned to integrate motor and reward-related information, in this process. To investigate this role, the activity of 126 neurons was recorded in the associative and limbic parts of the GPe of two monkeys perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
(68 reference statements)
3
16
0
Order By: Relevance
“…In contrast, the firing of the STN neurons fit better with an exponential function of their inputs (Bogacz and Gurney, 2007). This understanding is also consistent with in vivo electrophysiological studies in primates that report independent encoding of task variables by GPe neurons (Arkadir et al 2004;Nougaret and Ravel, 2018), suggesting more of a parallel processing of information by GPe neurons rather than an integration of different variables (Nougaret and Ravel, 2018). Taken together, these results are in line with the intermediate intrinsic timescale exhibited by the GPe in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the firing of the STN neurons fit better with an exponential function of their inputs (Bogacz and Gurney, 2007). This understanding is also consistent with in vivo electrophysiological studies in primates that report independent encoding of task variables by GPe neurons (Arkadir et al 2004;Nougaret and Ravel, 2018), suggesting more of a parallel processing of information by GPe neurons rather than an integration of different variables (Nougaret and Ravel, 2018). Taken together, these results are in line with the intermediate intrinsic timescale exhibited by the GPe in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The database we analyzed consisted of 78 neurons recorded in the STN (30 and 48 from monkey M and monkey Y, respectively); 158 PANs (96 and 62 from monkey M and monkey Y, respectively) recorded in the striatum, presumed to be medium spiny projection neurons (Inokawa et al, 2010); and 92 irregular neurons, corresponding to high-frequency discharge neurons (HFD;DeLong, 1971), from the GPe (41 and 51 from monkey M and monkey Y, respectively). Only neurons from the GPe were analyzed in a previous study (Nougaret and Ravel, 2018). Localizations of PANs in the striatum and STN neurons were assessed as in previous studies Ravel, 2015, 2018) using MRI scans with electrodes for locating trajectories, from which the neurons were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from pure motor function, the GPe is thought to integrate motor, cognitive, and reward‐related information . Recorded activity from GPe neurons in specific subregions revealed that activity of each different compartment is strongly influenced from the others: Few neurons of the GPe discharged encoding exclusively motor parameters, whereas most of them encoded both for motor parameters, force required (cognitive) and expected reward (limbic) . Nougaret and Ravel hypothesized that such convergence is highly suggestive of a role of the GPe in updating consequences of actions on motivational information .…”
Section: Discussionmentioning
confidence: 99%
“…65 Recorded activity from GPe neurons in specific subregions revealed that activity of each different compartment is strongly influenced from the others: Few neurons of the GPe discharged encoding exclusively motor parameters, whereas most of them encoded both for motor parameters, force required (cognitive) and expected reward (limbic). [66][67][68] Nougaret and Ravel hypothesized that such convergence is highly suggestive of a role of the GPe in updating consequences of actions on motivational information. 66 In this regard, our results from subareas analysis point out that sensorimotor information may reach the GPe from the postcentral gyrus, precentral gyrus, and paracentral lobule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation